An automatic air inflated tubeless safety jacket for motorbike riders. (22nd June 2021) - Bulathsinghala, Rameesh Lakshan; Fernando, Sandun; Jayawardana, Thantirige Sanath Siroshana; Heenkenda, Nilanthi; Jeyakumar, Sajeeva; Packiyarasa, Prathees; Hemamala, Gamage; Wijesena, Dhananatha
Abstract : Purpose: Motorcycle is one of the popular modes of transport in developing countries. However, the statistics related to accidents show that motorcycles are the most vulnerable vehicles. Research studies have revealed that half of all the possible types of motorcycle injuries could be reduced or prevented using effective protective clothing. Facts and figures emphasize that this is high time to develop a safety jacket for motorbike riders. This paper aims to develop an innovative, integrated automatic air-inflated tubeless jacket to prevent major injuries in fatal accidents. Design/methodology/approach: Two accelerometers integrated near the front axle, an angle sensor and the electronic control unit (ECU) were used to detect the collision or accident. The sensors were fixed on the bike and connected with the ECU via a bluetooth device that was always at the activated stage. The fused sensors were emulated with the ECU under laboratory conditions. The trigger signal generated by the crash discriminant algorithm triggered the chemical reaction to generate N2 gas and inflate the tubeless safety jacket. Findings: Under laboratory conditions, it was found that the signal generated by the ECU unit ejected approximately 15 litres of N2 gas in volume to fill the jacket within 100 milliseconds, which was less than the approximate estimated falling time of the rider 120 milliseconds. Originality/value: The existing developments of airbag systems in motorbikes are mounted on the motorbikes' frame, following the airbag systems in automobiles. These developments cannot fully protect the rider due to differentiation in crash dynamics and respective positions of the rider at the point of impact. Though few safety jackets and airbag vests are developed, the airbag deployment is activated when rider and motorbike separated during a collision using a tether-triggering mechanism. The authors designed the jacket so that inflation is activated not only by crash sensors but also on the fusion of multiple sensors based on a crash discriminative algorithm. The airbag deployment mechanism is incorporated with the jacket and acts as a safety jacket during a collision.